Crypto heist and data privacy issues: an analysis of the legal framework in Malaysia - Shahul Ikram, Nur Adlin Hanisah; Zul Kepli, Mohd Yazid (2021)
The occasional meteoric rise of cryptocurrency prices has led to increasing interest to buy crypto. Cryptocurrencies have entered a bull market and reached a new all-time high (ATH) in 2021. This has motivated cybercriminals to target the vulnerabilities of cryptocurrency platforms and digital wallets, resulting in many problems related to data privacy. One of the largest crypto heists took place in August 2021 whereby $600 million worth of crypto was stolen. This article highlights the legal issues and challenges related to the data protection and data security of cryptocurrencies. The analysis includes the standard expected from Malaysia’s legal regime on this matter and a comparison with the practice in the European Union and other advanced jurisdictions. This article proposes that the current legal framework must be improved to ensure better consumer and investors protection.